Hubungan Antara Komunikasi Interpersonal Kepala Sekolah Dengan Motivasi Kerja Pada Guru Sekolah SMP Islam Namira Medan - Agung Prasetyo; Syafrizaldi Syafrizaldi (Universitas Medan Area, 2023)
This study aims to see the correlation between the principal's interpersonal communication with work motivation on the teachers of SMP Islam Namira Medan. This research uses quantitative research methods. The sampling technique used was the Total Sampling Technique with a total of 30 people. Using the Likert scale technique, namely the interpersonal communication scale and work motivation scale. This analysis uses the Kolmogorov-Smirnov technique with the help of the SPSS version 25.0 computer program for Windows. used is if p 0.05 then it is declared normal and vice versa if p 0.05 then the distribution is declared abnormal. This means that the hypothesis proposed in this study is that there is a positive relationship between interpersonal communication and work motivation. That the principal's interpersonal communication is classified as very high. This can be seen from the comparison of the empirical average (74.73) which differs more than the SD number (15.803) with the hypothetical average value (72.5). Then work motivation is classified as very high. This can be seen from the comparison of the empirical average (70.43) which differs more than the SD number (17.399) with the hypothetical average value (62.5).